Karenia mikimotoi blooms in coastal waters of China from 1998 to 2017. (5th February 2021) - Baohong, Chen; Kang, Wang; Huige, Guo; Hui, Lin
Abstract: Karenia mikimotoi is a typical ichthyotoxic dinoflagellate species that causes blooms around the world. In China, the first K. mikimotoi bloom was recorded around the Pearl River estuary in 1998. There were 137 K. mikimotoi bloom events recorded in the four seas around China from 1998 to 2017. In the northernmost and southernmost regions, K. mikimotoi blooms occurred off of Qinhuangdao city and Zhanjiang city, respectively, with latitudinal range of approximately 20°. K. mikimotoi blooms were recorded almost every month from spring to autumn except November; however, no blooms occurred in winter during this 20-year period. In China, the 1998–2002 period represented the initial and developmental stages of K. mikimotoi blooms, while the 2003–2017 period represented the burst stage. Although large spatial and temporal distributions have been, K. mikimotoi blooms are generally centered on the period from May–June and on the coasts of the East China Sea, where the blooms have been correlated with conditions including eutrophication, meteorology and climate change, and sediment. Highlights: K. mikimotoi blooms occurred in a range of latitudes of about 20° in China. K. mikimotoi blooms preferred to occur in or around estuaries. K. mikimotoi blooms centralized in May–June and on Min-Zhe coasts in China. Eutrophication, rainfall and climate warming are important factors for the outbreak of K. mikimotoi blooms in China.